Flavonoids in Sepsis: Mechanistic Modulation of Inflammatory Pathways and Therapeutic Potential-A Systematic Review of Preclinical Studies - Yunita Dewani; Gusbakti Rusip; Boyke Marthin Simbolon (CoinReads Media Prima, 2026)
Introduction: Sepsis is a life-threatening syndrome driven by dysregulated host immunity, excessive inflammation, oxidative stress, endothelial injury, and immunosuppression. Flavonoids are bioactive polyphenols with anti-inflammatory and antioxidant effects; however, their therapeutic relevance in sepsis remains primarily preclinical. Methods: A systematic review was conducted using PubMed/MEDLINE, Scopus, Web of Science, and Embase to identify controlled in vivo studies that evaluated the effects of flavonoids in experimental sepsis or endotoxemia. Eligible studies compared flavonoid-treated animals with septic controls and reported survival, organ injury, inflammatory, oxidative, and mechanistic outcomes. Evidence was qualitatively synthesized, with survival findings contextualized using relevant preclinical meta-analytic data. Results: Eighty eligible studies were synthesized, predominantly rodent models using lipopolysaccharide-induced endotoxemia or cecal ligation and puncture. More than 30 flavonoids have been reported, including quercetin, kaempferol, luteolin, apigenin, fisetin, and orientin. Flavonoids reduce TNF-α, IL-6, IL-1β, oxidative stress, and organ injury in the pulmonary, renal, hepatic, and cardiovascular systems. Aggregated evidence suggests approximately 50% higher survival in flavonoid-treated animals. The mechanisms included NF-κB and MAPK inhibition, Nrf2/HO-1 activation, endothelial protection, and macrophage polarization. The limitations of this study include the prophylactic designs, heterogeneity, and limited clinical evidence. Conclusion: Flavonoids exhibit consistent multi-target immunomodulatory and organ-protective effects in experimental sepsis. Translation requires standardized post-insult studies, improved bioavailability, pharmacokinetic evaluation, and early phase clinical trials.